Semiconducting lanthanide polymers of pyridine-2, 6-dicarboxylate: Hydrothermal synthesis, structural characterization, electrical conductivity and luminescence properties. (1st March 2018) - Ay, Burak; Yildiz, Emel; Kani, İbrahim
Graphical abstract: Two novel 3D lanthanide-organic framework have been synthesized under hydrothermal conditions. The thermal behavior, luminescence and electrical conductivities of1 –2 were investigated.1 and2 showed excellent electrical conductivity values of 9.4 × 10 −4 and 9.7 × 10 −4 S·cm −1 at room temperature, respectively. Photoluminescent spectra of the1 and2 show that compounds are the potential luminescent materials at the maximum emission 612 and 624 nm, respectively. Abstract: This paper describes the hydrothermal synthesis of two novel lanthanide coordination polymers (CPs) (H2 pip) n [Ln2 (pydc)4 (H2 O)2 ] n (Ln = La (1 ) and Nd (2 ), H2 pydc = 2, 6-pyridinedicarboxylic acid, H2 pip = piperazine). The synthesized polymers were structurally characterized by the elemental analysis, ICP-OES, IR spectroscopy, TGA, single-crystal X-ray diffraction and powder X-ray diffraction (PXRD) analysis. For the morphological analysis field emission scanning electron microscopy (FESEM) was used. CPs are isomorphous, showing three-dimensional Ln–O–Ln chains. Ln(III) ions in1 –2 adopt nine-coordinated mode to construct a mono-capped square antiprism coordination environments. The electrical conductivity and luminescence properties of insoluble1 –2 have been investigated. CPs exhibited luminescence emission bands at 612 nm for1 and 624 nm for2 at room temperature when excited at 320 nm.